Giant optical activity of helical architectures of plasmonic nanorods - semiramis vevelogianni; N. Stefanou; A.Christofi; N. Papanikolaou (Journal of Physical Chemistry C, 2012)
A systematic study, by means of full electrodynamic calculations, of the optical activity of layer-by-layer chiral crystals of finite silver nanorods is presented. The nature of the eigenmodes of the electromagnetic field and the formation of partial gaps for a specific circular polarization in these crystals are analyzed by reference to the hybrid plasmon modes of the structural basis of twisted nanorods. It is shown that collective plasmon modes of the helical assembly give rise to giant optical activity effects, which persist for any angle of incidence and polarization direction. The effects, which are robust against the twisting angle and become more pronounced with increasing particle concentration, can be tuned within a broad range of frequencies in the infrared and visible spectrum by appropriately choosing the rod length. Potential applications of these structures for polarization control in subwavelength optical components are anticipated.